(untitled) (Singapore, 2007)
Two major educational developments have gained significant momentum in recent years: the adoption of problem-based learning (PBL) as an educational innovation and the use of web technologies to support learning. In this volume, leading practitioners and researchers worldwide consider the limitless possibilities of ePBL. They provide a wealth of ideas, models, and examples related to the design, implementation, and evaluation of ePBL
Keywords: Problem-based learning.,Computer-assisted instruction.,Internet in education.,Education; Computer network resources